Development and application of a social accountability assessment tool at the Shahid Beheshti University of Medical Sciences - Shahram Yazdani; Sedigheh Momeni; Mahsa Shakour; Reza Abdolmaleki (Tabriz University of Medical Sciences, 2022)
Background: One of the critical needs of governmental agencies and educational institutions is meeting community needs. Organizations and governmental systems that rely on social capital are considered inefficient and vulnerable if they are unable to meet the needs of society. Thus, accountability is a critical pillar of government management that leads to effective actions and better service delivery. Methods: Critical review methodology was used in the first phase to review texts and documents available in the field of social accountability and to collect items used to develop the social accountability assessment tool. The Delphi method was then used to finalize and approve the model and assessment tool. University processes were investigated and evaluated based on the social accountability tool in the second phase. Result: In all, 422 university processes were investigated and evaluated to determine their accountability in different fields. The mean score of the evaluated processes was 11.9 out of 100. Conclusion: The results show that social accountability is a relatively new topic that has received considerable attention in medical education in Iran. Given the relative newness of this topic, these results could be expected; social accountability should try and be expected to improve in the coming years.